Um estudo sobre códigos de conduta e risco corporativo - Ayres, Paulo Roberto Reichelt (Universidade do Vale do Rio dos Sinos, 2016)
From time to time, issues related to corporate governance gained greater prominence in the business environment. Usually, the result of financial scandals and acts of corruption involving large organizations, the discussions on good governance practices, such as audit committees and risk management, creating areas of internal control and implementation of codes of conduct, re-emerging in the economic scenario . The Code of Conduct is an integral part of a management control system, making the link with the corporate governance process, assisting in raising the ethical standards of the organization and thus improving investor confidence. So, this study aimed to study whether there is a relationship between codes of conduct and corporate risk. Therefore, we performed the choice of a stock index of BM & F BOVESPA and proceeded to read all the codes of conduct of the companies that make up this index. Additionally, Economática database was used for stock volatility of this index (considered a risk proxy) and also the control variables used in the econometric model. Adopted the content analysis method to convert text to numeric variables, aimed at further quantitative evaluation data. Based on the results reported by multiple linear regression equation, there is no statistically significant relationship between codes of conduct and risk. The p-value calculated was much above 5% and the use of codes of conduct can not explain the level of risk posed by the organizations. This result may have been influenced by the choice of stock volatility as a risk proxy. Moreover, it is possible that only the code of conduct, recognized as an instrument of a management control system, is not sufficient to explain the level of risk of the companies analyzed.
Keywords: Código de conduta; Sistema de controle de gestão; Governança corporativa; Ética; Code of conduct; Management control system; Corporate governance; Ethic; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis